Length-weight relationship of dominant fish species of two medium reservoirs of Uttarakhand, India - Mishra, Ashutosh; Chakraborty, S. K.; Jaiswar, A. K.; Sharma, A. P. (Indian Journal of Fisheries, 2018)
Length-weight relationship of dominant fish species namely, Labeo rohita, Labeo gonius, Cirrhinus mrigala and Wallago attu of two medium reservoirs viz., Dhaura and Baigul located in Tarai region of Uttarakhand were studied. There was a positive correlation between length and weight among these fishes. The values of coefficient of determination (R2) and slope (b) in the length-weight relationship ranged from 0.7994 to 0.9591 and from 2.3089 to 3.0627 respectively for fishes from Dhaura Reservoir and from 0.7694 to 0.9843 and from 2.4272 to 3.2286 respectively for fishes of Baigul Reservoir. The condition of the fishes of Baigul Reservoir was better than Dhaura in relation to length and weight.